2020
DOI: 10.1101/2020.07.08.191072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous flexibility analysis of SARS-CoV-2 Spike prefusion structures

Abstract: AbstractWith the help of novel processing workflows and algorithms, we have obtained a better understanding of the flexibility and conformational dynamics of the SARS-CoV-2 spike in the prefusion state. We have re-analyzed previous cryo-EM data combining 3D clustering approaches with ways to explore a continuous flexibility space based on 3D Principal Component Analysis. These advanced analyses revealed a concerted motion involving the receptor-binding domain (RBD), N-terminal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 45 publications
(72 reference statements)
7
31
0
Order By: Relevance
“…It is unclear if any additional conformational states other than those with either all three RBD domains in the closed state or only one RBD open state are biologically relevant. Specifically, Yurkovetskiy et al [44] observed an occupancy for states with two or three RBD domains in the open conformation, but these were not observed by Gobeil et al [30] and Xiong et al [32] or taken into consideration in several other structural studies [20][21][22][23][24]. As such, we employ the two-state model shown in Figure 2 We utilized this data to calculate occupancy differences for each variant (Figure 9).…”
Section: Conformational State Occupanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if any additional conformational states other than those with either all three RBD domains in the closed state or only one RBD open state are biologically relevant. Specifically, Yurkovetskiy et al [44] observed an occupancy for states with two or three RBD domains in the open conformation, but these were not observed by Gobeil et al [30] and Xiong et al [32] or taken into consideration in several other structural studies [20][21][22][23][24]. As such, we employ the two-state model shown in Figure 2 We utilized this data to calculate occupancy differences for each variant (Figure 9).…”
Section: Conformational State Occupanciesmentioning
confidence: 99%
“…Several aspects of the dynamics of the Spike protein are being currently studied, with a range of particular goals: to evaluate the docking of small molecules to the RBD domain [19], to search for alternative target binding-sites for vaccine development [20], to understand residue-residue interactions and their effects on conformational plasticity [21] and to investigate the flexibility of different domains in particular conformational states [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, owing to a pivotal role of S protein in eliciting the infection cascade, it is the most well-characterized viral structural protein and is widely used to isolate neutralizing antibodies ( Du et al., 2009 ; Elshabrawy et al., 2012 ; Jiang et al., 2014 ; Li et al., 2015 ; Wang et al., 2015 ; Ying et al., 2015 ; Yu et al., 2015 ). A large number of structural studies indicate appreciable flexibility of the RBD region and unequivocally report the presence of the distinct 1-RBD up-open and all-RBD down-closed species of S protein trimers ( Ke et al., 2020 ; Korber et al., 2020 ; Melero et al., 2020 ; Walls et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequently deposited PDB structure (PDB ID 6X2B (Henderson et al, 2020)) revealed two upwards protruding RBDs; however, only a single RBD is necessary for ACE2 binding. It is not yet known if protrusion of the RBD from the S-protein trimer is necessary for binding to ACE2 or, as a recent meta-analysis of cryo-EM data suggests (Melero et al, 2020) that interconversion of the RBD between closed and open states represents an intrinsic property of the S-protein. Structures of the S-protein RBD were determined by X-ray crystallography early in the pandemic, both bound to full-length ACE2 receptor (PDB ID 6M17 (Yan et al, 2020)) and bound to relevant ACE2 binding domains (PDB ID 6M0J (Lan et al, 2020); PDB ID 6LZG (Q.…”
Section: Resultsmentioning
confidence: 99%